The prevalence of lower urinary tract symptoms based on individual and clinical parameters in patients with multiple sclerosis - Fatemeh Nazari; Vahid Shaygannejad; Mehrdad Mohammadi Sichani; Marjan Mansourian; Valiollah Hajhashemi (BMC Neurology, 2020)
Abstract Background Most patients with multiple sclerosis (MS) suffer from bladder dysfunction during the course of the disease. This study was conducted to examine the prevalence of these complications among patients with MS. Methods This cross-sectional study was performed on 602 patients with MS who referred to the neurology clinics of Kashani and Alzahra Hospitals affiliated to Isfahan University of Medical Sciences, Isfahan, Iran. Multistage random cluster sampling was performed and the informed consent form was signed by the subjects. Then, all the data were collected through interviews using the Lower Urinary Tract Symptom Score (LUTSS) developed in accordance with the definitions presented by the International Continence Society (ICS) and the International Prostate Symptom Score (I-PSS) and DASS-21 questionnaire. The data were analyzed using descriptive and inferential statistical tests in SPSS. Results The prevalence rate of lower urinary tract symptoms (LUTS) was 87.6% among all the subjects, with a similar rate among women (88.0%) and men (86.0%). There was a significant difference between men and women in terms of the prevalence of stress urinary incontinence (SUI), intermittent urine flow, hesitancy, straining, and dribbling (P <  0.050). There was no significant difference between women and men in terms of the prevalence of other symptoms (P > 0.050). A significant difference was observed in the degree of LUTS with age, marital status, marriage duration, education, illness duration, clinical course, disability, anxiety, depression, and stress (P<  0.05). Moreover, logistic regression analysis revealed that there was a higher probability of a urinary problems among patients with MS and a high EDSS score [0.67 (0.507–0.903), P = 0.008]. Conclusions A high prevalence of LUTS was found among patients with MS. There was a higher probability of a urinary tract problem among patients with MS and a high EDSS score. Therefore, it is recommended that the health system take the necessary measures regarding timely detection and treatment of LUTS among these patients in order to prevent secondary outcomes and improve the quality of life (QOL) of patients with MS.